Tradition Meets Modernity: A Study on Classic Book (Turats) Learning at Sidogiri Pesantren - Zen Amrullah; Siti Mutholingah Mutholingah (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
This study investigated the design, implementation, and implications of classical book (turats) learning tools within the educational framework of Sidogiri Pesantren. Employing a qualitative case study approach, data were collected through interviews, focus group discussions, documentation, and observation, and analyzed using an interactive model. The findings reveal that the curriculum and teaching materials for turats learning were collaboratively developed by the Tarbiyah wa Ta’lim Madrasy board (Batartama) and the teaching staff. The instructional process followed a structured sequence—comprising opening, core, and closing activities—while allowing teachers pedagogical flexibility during the core phase. Evaluation focused on both learning outcomes and instructional processes, ensuring a comprehensive assessment of student progress. The implementation of this model fostered an engaging learning environment and enhanced students’ competencies in reading classical texts, as evidenced by their achievements in various turats competitions. The study’s novelty lies in its hybrid learning model, which integrates traditional salaf methodologies with modern pedagogical principles, emphasizing systematic instructional design. Academically, this research contributes a new framework for Islamic education, offering a balanced approach that preserves heritage while embracing innovation. Practically, it serves as a guide for other pesantren seeking to improve the effectiveness of their classical book curricula through structured planning, adaptive teaching strategies, and outcome-oriented evaluation systems.